Evaluation of a crescent saw guide for tibial plateau‐leveling osteotomy: An ex vivo study. Issue 3 (16th February 2022) - Peterson, Lindsay C.; Kim, Stanley E.; Biedrzycki, Adam H.
Abstract: Objective: To evaluate the effectiveness of a novel crescent‐shaped tibial plateau‐leveling osteotomy (TPLO) saw guide (crescent guide) to assist with saw control in novice participants. Study design: Ex vivo study. Sample population: Synthetic bones ( n  = 54) and medium sized dog pelvic limbs ( n  = 36). Methods: The 6 participants (interns and residents) without any prior experience performing a TPLO each performed 9 osteotomies on synthetic tibia models, and 6 osteotomies in cadaveric limbs of medium‐sized dogs. Osteotomies made with the crescent guide were compared with those made with a standard jig and a radial saw guide with a jig. Osteotomy angulation, distance of eccentricity (DOE), and medial tibial cortical damage (synthetic bone models only) were measured from calibrated photographs. Participants rated their experiences with each technique. Results: There was no difference in the DOE, coronal or axial osteotomy angulation between the 3 alignment devices for synthetic bone models or cadavers. Average medial cortical damage with the crescent guide (3.8 ± 7.3 mm 2 ) was lower than with the radial guide (35.7 ± 27 mm 2 ) and standard jig (51.2 ± 63.2 mm 2 ) guides ( P  = <.01). Five of 6 participants preferred the crescent guide over the standard jig and radial guide. Conclusion: There was no difference in accuracy of osteotomy positioning but using the crescent guide resulted in lower cortical damage and more favorable participant perceptions. Clinical relevance: The crescent guide may improve control of the radial saw during TPLO in novice surgeons but does not appear to aid accurate osteotomy positioning.